Social Media Utilization In Umkm Marketing Strategy : A Digital Media Optimization Framework (Case Study: Miami Cafe and Restaurant): - Andriani, Meta; Hutauruk, Sara Immanuella; kasman, Muh. Nurdin Nur Abdi; Yasin, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2024)
The object of this community service is Micro, Small and Medium Enterprises (MSMEs), namely Resto and Cafe Miami located in Kemang Raya, South Jakarta. This business, which has only been established for approximately 5 months, certainly needs assistance in developing its business, especially in the marketing sector. In this Community Service activity, MSMEs are assisted in creating social media accounts such as Instagram and Tiktok, and are given assistance in managing these media through good content. The method used in this activity is training such as guides or tutorials. As for the results obtained from this activity, that assistance in managing social media as a digital marketing strategy should be continued regularly so that the results are optimal and have a significant impact on MSME sales activities.